Taphofacies of Lower-Middle Pennsylvanian marine invertebrates from the Monte Alegre and Itaituba formations, part of the outcropped marine sequence of the Tapajós Group (Southern Amazonas Basin, Brazil) – regional palaeoecological models. (October 2016) - Moutinho, L.P.; Scomazzon, A.K.; Nascimento, S.; Lemos, V.B.
Abstract: One of the most relevant characteristics of the Pennsylvanian shallow-water carbonates of the Amazonas Basin is its diverse and well preserved invertebrate fossiliferous assemblages. In order to better understand the origin of these fossil concentrations, taphonomic data were obtained along well exposed areas of the uppermost part of the Monte Alegre Formation and basal part of the Itaituba Formation, which, based on conodonts, fusulinids and palynomorphs is of Atokan age. The taphonomic data focused on invertebrate organisms were supported by petrographic analysis. The understanding of the stacking pattern of the strata in the studied section allowed the identification of five type taphofacies, which contributed in the development of regional palaeoecological models, expressed as block-diagrams. These characterize the distribution of the environmental parameters, the composition of the faunal associations and the distribution and amplitude of the taphonomic processes that created the taphonomic signatures of the bioclastic elements throughout the supratidal to lower intertidal/deep subtidal depositional environments pertinent to the studied depositional environment. The regional palaeoecological models here presented are related to the particularities of the depositional environments of the studied rocks and are exclusive for the characterization of this intracratonic basin set influenced by high frequency climatic variations. Lithofacies, biofacies and taphofacies associations also reflect depositional conditions pertinent to the studied regional context, differing from the elements observed in modern intracratonic contexts analogous to the one studied, from different sedimentary basins around the world. Therefore, invertebrate taphonomy, supported by the analysis of sedimentary facies, fulfills the purposes recommended in this work, demonstrating its potential as a tool for palaeoecological analysis in the Pennsylvanian outcropping section in the southern platform of the Amazonas Basin. Graphical abstract: Highlights: Invertebrate's taphonomy as a palaeoecological tool for the Pennsylvanian of the Amazonas Basin. Shallow marine and invertebrates' rich carbonate deposits of Monte Alegre and Itaituba Formations. Taphonomy focused on well preserved invertebrate fossiliferous assemblages. Taphofacies contributed in the development of regional palaeoecological models. Environmental parameters, faunal associations and taphonomic process observed.